ANALISIS TRANSKRIPTOMIK UNTUK MENDESKRIPSIKAN PENGARUH PENYALUTAN KITOSAN TERHADAP EKSPRESI KELOMPOK GEN METABOLISME KLOROFIL SELAMA PEMATANGAN PISANG CAVENDISH (MUSA ACUMINATA âCAVENDISHâ, AAA) - Ganang Prisbiyanto, Reffa
Banana is a climacteric fruit whose ripening process can occur quickly and is susceptible to post-harvest damage. One of the mechanisms that occur during banana ripening is chlorophyll degradation. Chlorophyll metabolism includes biosynthetic and degradation processes involving various intermediate catabolites. One of the intermediate catabolites is chlorophyllide in chlorophyll biosynthesis which has the ability as an antioxidant, antiviral, and antimicrobial that can help fruit defense during the fruit ripening process. Based on previous research, chitosan is often applied to inhibit fruit ripening because it has antimicrobial, antifungal, biodegradable, non-toxic, and moisture absorption abilities. So it is suspected that the chitosan coating will affect the expression level of the chlorophyll metabolism gene group. Research on the effect of chitosan coating on chlorophyll metabolism in fruit flesh during banana fruit ripening at the gene level using a transcriptomic approach is still not well defined until now. This study was conducted to determine the effect of chitosan coating on the expression level of chlorophyll metabolism gene groups in fruit flesh during the ripening process of Musa acuminata 'Cavendish' fruit. The secondary data used were the results of RNA-seq of Musa acuminata 'Cavendish' fruit on the first and seventh days of control and chitosan treatment. Identification of differencial expressed gene (DEG) was performed using the Tuxedo method, and visualized with CummeRbund. Functional annotation analysis and enrichment analysis were performed with the KEGG database alignment. Based on the results of the analysis, the pattern of gene expression related to chlorophyll metabolism in the fruit ripening process in the control treatment (7K/1K) and chitosan (7A/1A) showed the same pattern, which led to the reduction of pigmented catabolites, accumulation of chlorophyllide, and degradation of chlorophyll. The effect of chitosan related to the expression of chlorophyll metabolism genes is shown by an expression pattern that is always opposite to the ripening process, indicating that the fruit still retains pigment with chlorophyll biosynthesis, reducing gene expression related to chlorophyllide synthesis presumably because chitosan has antioxidant and antimicrobial properties similar to chlorophyllide so it can provide protection to fruit, as well as reducing the expression of chlorophyll degradation genes. Significantly upregulated gene expression differences (1A/1K & 7A/7K) were the genes Ma02_g04400, Ma11_g23950, Ma10_g16570, Ma10_g26330, Ma09_g29720. While the down-regulated is Ma06_g24000.